Interactions between gut microbiota and the central nervous system, with emphasis on quorum sensing between commensal lactic acid bacteria and human cells - Dicks, Leon Milner Theodore (Stellenbosch : Stellenbosch University, 2023)
Thesis (PhD)--Stellenbosch University, 2023.